Rupture of the tibialis posterior tendon: an important differential in the assessment of ankle injuries. Issue 12 (18th November 2005) - Foster, A P; Thompson, N W; Crone, M D; Charlwood, A P
Abstract : Rupture of the tibialis posterior tendon can be missed. We report a case of posterior tibialis tendon rupture that, owing to misdiagnosis, resulted in a significant foot deformity requiring arthrodesis for chronic pain.